Bridging Legal Commitments and Migrant Vulnerabilities: KBRI Kuala Lumpur’s Educational Policies from the Perspective of Islamic Legal Maxims - M. Azka Zulfar Rohman; Fatmah Fatmah (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study examines the policy of the Embassy of the Republic of Indonesia (KBRI) in Kuala Lumpur in fulfilling the educational rights of children of Indonesian Migrant Workers (PMI) through the Islamic legal maxim taṣarruf al-imām ‘alā al-ra‘iyyah manūṭun bi al-maṣlaḥah, which emphasizes that state policies must be oriented toward public welfare. The study is motivated by the gap between normative legal guarantees and empirical realities, where many migrant children in Malaysia still face restricted access to education due to undocumented status, administrative obstacles, and social vulnerability. Employing a normative-empirical legal research method with statutory and conceptual approaches, data were collected through document analysis, semi-structured interviews, and limited observations. The findings reveal that KBRI Kuala Lumpur’s educational policies, implemented through the Indonesian School of Kuala Lumpur (SIKL), Distance Learning Programs (PJJ), Sanggar Bimbingan, and the ADEM and ADIK affirmative scholarship programs, form an adaptive framework for expanding educational access for migrant children. The study’s novelty lies in demonstrating that these policies function not merely as administrative services, but as legal instruments of state protection that bridge normative commitments and the structural vulnerabilities of undocumented migrant communities. Accordingly, the maxim serves both as an ethical principle of governance and as a legal framework for evaluating the legitimacy and protective orientation of state policies toward vulnerable citizens abroad.